Supercapacitor electrode based on three-dimensional graphene–polyaniline hybrid - Dong, Xiaochen (2013)
Three-dimensional (3D) graphene was synthesized by chemical vapour deposition with nickel foam as a substrate. Based on the 3D graphene foams, free-standing graphene–polyaniline (PANI) hybrids were produced by in-situ polymerization of aniline monomer under acid condition, and characterized by scanning electron microscopy (SEM), Fourier transformation infrared (FTIR), and Raman spectroscopy. Furthermore, we show that supercapacitor electrodes based on the 3D graphene–PANI hybrid exhibit high specific capacitances (346 Fg−1 at a discharge current density of 4 Ag−1), suggesting that the light and inexpensive 3D graphene foams are a promising candidate for energy storage.